The Impact of Systemic Therapy Beyond First-line Treatment for Advanced Cervical Cancer. Issue 3 (March 2017) - McLachlan, J.; Boussios, S.; Okines, A.; Glaessgen, D.; Bodlar, S.; Kalaitzaki, R.; Taylor, A.; Lalondrelle, S.; Gore, M.; Kaye, S.; Banerjee, S.
Abstract: Aims: Despite recent advances in the primary and secondary prevention of cervical cancer, a significant number of women present with or develop metastatic disease. There is currently no consensus on the standard of care for second-line systemic treatment of recurrent/metastatic cervical cancer. The purpose of this study was to evaluate the second-line systemic therapy used and the associated outcomes in a single cancer centre. Materials and methods: A retrospective review of patients with cervical cancer who received one or more lines of treatment for recurrent or metastatic cervical cancer at the Royal Marsden Hospital between 2004 and 2014 was carried out. The primary objective was to establish the types of second-line systemic treatment used. Secondary end points included objective response rate, progression-free survival and overall survival after second-line therapy. Results: In total, 75 patients were included in the study; 53 patients (70.7%) received second-line therapy for recurrent/metastatic disease. The most common second-line therapy was weekly paclitaxel (28.3%). Carboplatin-based chemotherapy (24.5%), targeted agent monotherapy within clinical trials (22.6%), docetaxel-based chemotherapy (13.2%), topotecan (9.4%) and gemcitabine (1.9%) were also used. The objective response rate to second-line therapy was 13.2%, which included three partial responses to carboplatin and paclitaxel, two partial responses to docetaxel-based chemotherapy, one partial response to weekly paclitaxel and one partial response to cediranib. Twenty-two patients (41.5%) achieved stable disease at 4 months. The median progression-free survival for women treated with second-line therapy was 3.2 months (95% confidence interval 2.1–4.3) and median overall survival was 9.3 months (95% confidence interval 6.4–12.5). Thirty-nine per cent of patients received third-line therapy. Conclusion: Seventy per cent of patients treated with first-line systemic therapy for recurrent/metastatic cervical cancer subsequently received second-line treatment but response rates were poor. There remains no standard of care for second-line systemic therapy for advanced cervical cancer. Patients should be considered for clinical trials whenever feasible, including novel targeted agents and immunotherapy. Highlights: There is no standard of care for second-line systemic therapy for advanced cervical cancer. The objective response rate to second-line systemic therapy in this study was low, < 15%. Patients should be considered for clinical trials, including novel targeted agents and immunotherapy.